Advances in the therapeutic approach to fibromyalgia: an integrative review (Research, Society and Development, 2022)
Fibromyalgia (FM) is a syndrome characterized as a complex systemic disorder, which affects millions of people around the world, leading to an increase in the use of non-pharmacological therapies, as therapeutic measures with fewer side effects and with the aim of a better approach. more effective than FM. The present review study sought to evaluate new advances in the therapeutic approach to fibromyalgia, documented through clinical and randomized studies. This is an integrative review research carried out through the PubMed database, which took into account the following inclusion criteria: clinical trials and controlled and randomized trials; articles published in the last year that had full text available and that addressed the treatment of fibromyalgia. It was observed that the practice of central muscle strengthening, stretching and whole-body vibration proved to be beneficial in improving quality of life, as well as group interventions that focus on self-care and pain neuroscience education. Interventional therapies such as transcranial direct current stimulation have shown disagreements as to the effectiveness of the method, and a Khorasan wheat replacement diet resulted in an overall improvement in gastrointestinal symptoms seen in fibromyalgia patients. Spironolactone and allopurinol were ineffective, unlike vitamin B6 and magnesium supplementation, both related to pain improvement and stress reduction, respectively, in patients with fibromyalgia. Thus, new studies that allow the effective understanding of such therapeutic modalities in the management of fibromyalgia are suggested by the authors.